PERLINDUNGAN ANAK PEREMPUAN KORBAN KEKERASAN SEKSUAL DI KABUPATEN SUMBAWA - Apriadi; Dwi Cahyono , Tomy (Fakultas Psikologi - Universitas Teknologi Sumbawa, 2019)
Sexual abuse on children has become a national issue in Indonesia, especially for girls who are more vulnerable to sexual abuse by adult. Therefore, guidance and protection of children's rights is needed, especially in guaranteeing their social, mental and physical development. The purpose of this study was to determine the problems and efforts to protect children, the victims of sexual abuse in Sumbawa Regency. The method used to achieve the goal is to use a qualitative approach with the type of descriptive research that is describing the problem of child victims of sexual abuse and protection efforts by the Sumbawa government. The results of this study are the protection of girls, the victims of sexual abuse in Sumbawa which  has not been running optimally, due to several factors; (1) victims' families, especially those living in rural areas prefer to solve problems with a family based on shame, (2) limited field workers from P2TP2A or Sumbawa LPA so that they cannot reach victims in remote areas, (3) budget limitations especially for post mortem for victims for court purposes and the absence of a Safe House so that victims are returned to the family home.